RRB Indian Railway Non-Technical Recruitment Examination :NTPC-Non-Technical Polpular Categories - C. V. Jayanna (Bengaluru Sapna Book House, 2024)
Mathematics and Arithmatic Ability--General Intelligence and Mental Ability--General Knowledge.
English
Keywords: Compitative Exams; Recruitments; RRB